dachshund encodes a nuclear protein required for normal eye and leg development in Drosophila. - Mardon, G.; Solomon, N.M.; Rubin, G.M. (Development, 1994)
Neural specification and differentiation in the Drosophila eye sweep across the unpatterned epithelial monolayer of the eye imaginal disc following a developmental wave termed the morphogenetic furrow. The furrow begins at the posterior margin of the eye imaginal disc and moves anteriorly as a linear front. Progression of the furrow requires the function of hedgehog, which encodes a secreted signaling protein. We characterize mutations in dachshund, a gene that encodes a novel nuclear protein required for normal cell-fate determination of imaginal disc cells. In the absence of dachshund function, cells at the posterior margin of the eye disc fail to follow a retinal differentiation pathway and appear to adopt a cuticle fate instead. These cells are therefore unable to respond to pattern propagation signals such as hedgehog and furrow initiation does not occur. In contrast, cells in more anterior portions of the eye disc are able to differentiate as retinal cells in the absence of dachshund activity and respond normally to patterning signals. These results suggest that posterior margin cells are distinct from other cells of the eye imaginal disc by early stages of development. dachshund is also necessary for proper differentiation of a subset of segments in the developing leg. Null mutations in dachshund result in flies with no eyes and shortened legs.